Effects of Metformin on Biochemical Marker of Recurrence Among Post Mastectomy Female Diabetic Patients (Journal of Dhaka Medical College, 2018)
Background: The different modalities of the treatment of diabetes such as life style modification, metformin, insulin and combination of metformin & insulin have role on breast cancer outcome. Insulin and metformin have some influence on the outcome indirectly by affecting some biochemical markers such as S. adiponectin, HOMA IR & IGF-I. Therefore this study investigates the effect of metformin and insulin in postsurgical breast cancer patients which is evaluated by S. adiponectin levels and their association with obesity.Objectives: To evaluate effects of metformin on biochemical marker of recurrence among post mastectomy female diabetic patients.Materials and methods: It was a retrospective cohort study done in Sir Salimullah Medical College and Mitford Hospital Dhaka, from January 2015 to December 2015. In this study purposive consecutive samples were collected at base line from 3 months to 36 months post mastertomy. After fulfill all exclusion and inclusion criteria, 82 cases were selected as sample.Results: Mean age was found 47.2 years with ranging from 26 to 75 years. Only 9(11.0%) respondents had family history. The mean BMI was 28.4 kg/m2 and mean waist circumference was 95.2 cm. Almost half (48.8%) respondents took oral contraceptive pill and post menopausal status was found in 48(58.5%) respondents. The mean S. adiponectin level was statistically significant when compared with different type of DM treatment and different BMI group.Conclusion: This study finally focused that the effects of metformin; the antidiabetic medication has play an important role to change the S. adiponectin level which modify the outcome among post mastectomy diabetic patients. The recurrence can’t be evaluated clinically due to short period of time and need a further study for follow up.J Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 41-46